Luminescent quantum dots encapsulated by zwitterionic amphi philic polymer: surface charge-dependent interaction with cancer cells - Petrova, Elena A.; Terpinskaya, Tatiana I.; Artemyev, Mikhail V.; Fedosyuk, Aleksandra A.; Radchanka, Aliaksandra V.; Antanovich, Artsiom V.; Prudnikau, Anatol V. (Journal of the Belarusian State University. Chemistry, 2018)
Here, we prepared water-soluble highly luminescent CdSe/ZnS quantum dots having different surface charge and examined how zeta potential of quantum dots affected their uptake by cancer cells. Water soluble quantum dots with varied zeta potential were prepared through encapsulation with amphiphilic polymer poly(maleic anhydride-alt-1-tetradecene) (PMAT) containing ziwitterions formed by spatially separated carboxyl and quaternary amino groups. Varying the ration of negatively charged carboxyl and positively charged quaternary amino-groups during chemical modification of PMAT we control the sign and magnitude of zeta potential of encapsulated quantum dots. Quantum dots having nearly equal amount of carboxyl and quaternary amino groups possess pH-controlled zeta potential which can vary from negative to positive value when pH changes from basic to acidic condition. Cellular uptake of encapsulated quantum dots has been found to be strongly dependent of their surface charge: positively charged quantum dots efficiently internalized by cells, while negatively charged adsorbed mostly at the cell membrane. Zwitterionic QDs do not demonstrate any charge-dependent cellular toxicity at least within few hours. Long-term incubation of cells stained with zwitterionic quantum dots results in the decrease of the fluorescence signal mainly due to the cell proliferation.